Neurorestorative effects of sub-chronic administration of ambroxol in rodent model of Parkinson’s disease - Mishra A.; Krishnamurthy S. (My University, 2025)
Disease-modifying agents are unmet medical need for Parkinson’s disease (PD). Drugs are under clinical trial to halt its progression, such as ambroxol due to its glucocerebrosidase (GCase)-stimulating activity. However, the neurorestorative effect of ambroxol is not yet investigated in any of the well-established PD models in vivo. Ambroxol was administered as 400 mg/kg orally twice a day from D-28 to D-70 after the unilateral intrastriatal injection of 6-hydroxydopamine (6-OHDA) in male rats. Behavioral parameters were observed every week, and at last, tyrosine hydroxylase (TH), dopamine transporter (DAT), glucocerbrosidase (GCase) enzymatic and mitochondrial complex-I activity, α-synuclein levels, and Nissl’s staining were performed. Behavioral functions were progressively recovered. Ambroxol restored TH and DAT levels on D-71 as the markers of dopaminergic cell and extracellular DA concentration respectively, indicating the recovery of dopaminergic system. Factors involved in PD pathogenesis such as GCase enzymatic and mitochondrial complex-I activity were restored, and α-synuclein pathology was decreased by ambroxol. GCase deficiency is involved in mitochondrial impairment and formation of oligomeric α-synuclein aggregates which negatively affect mitochondrial function. Nissl bodies were also normalized. Therefore, both the GCase-stimulating and α-synuclein pathology-diminishing effects of ambroxol may be responsible for increment in mitochondrial function and restoration of dopaminergic system. These may act as significant mechanisms for disease-modifying potential of ambroxol. The current study provides the preclinical evidence to support the neurorestorative potential of ambroxol in 6-OHDA-induced hemiparkinson’s rat model and indicates its possible use as disease-modifying agent in PD. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.